(untitled) (Nigerian Journal of Technology, 2015)
The effect of biodiesel and its blends synthesized from coconut oil (CNO) via alkali catalyzed transeterification on the key fuel properties and corrosion characteristics of copper were investigated. The transesterification of the CNO via ethanol in the presence of potassium hydroxide was performed and the resulting coconut oil ethyl ester (COEE) was blended with fossil diesel (B0). The fuel properties such as density, kinematic viscosity (KV), pour and cloud points (PP and CP, respectively) and American Petroleum Institute of Gravity (API) of B0, COEE-diesel blend (B50) and COEE (B100) were characterized and compared with that of ASTM D6751 and EN14214 standards. Static immersion tests were conducted by exposing copper coupons toB0, B50 and B100 at different temperatures (50, 65 and 80 oC) for 5 days. Corrosion rates of copper in these fuels were determined by weight loss method. Also, during the period of investigation, these fuels were analyzed by measuring total acid number (TAN). The results showed that the density, KV, PP and CPincreased while the API gravity decreased as the percentage of the biodiesel in the blend increased. The highest corrosion rates for copper at the end of the investigation were 0.054, 0.0954 and 0.139 mpy in B0, B50 and B100, respectively. The minimum TAN (0.17 mg KOH/g) and maximum TAN (0.62 mg KOH/g) were observed in B0 and B100 containing copper, respectively. http://dx.doi.org/10.4314/njt.v35i1.17